Conformal phase transition in supersymmetric QCD - Kohei Fujikura; Shota Nakagawa; Yuichiro Nakai; Peng Sun; Yufei Zhang (Journal of High Energy Physics)
Abstract We construct a four-dimensional supersymmetric QCD in conformal window with a marginally relevant deformation which triggers the spontaneous breaking of (approximate) scale invariance and the subsequent confinement, generating a mass gap, at an energy scale hierarchically smaller than the Planck scale without fine-tuning. We analyze the finite temperature system and show that the phase transition associated with the breaking of conformal invariance is of the strong first order. When such a phase transition takes place at a temperature of the Universe around the electroweak scale, it generates a stochastic gravitational wave (GW) background probed by future space-based interferometers, while a conformal phase transition in a dark sector at O 1 $$ \mathcal{O}(1) $$ GeV generates GWs to explain the reported pulsar timing array signal.